1997
DOI: 10.3758/bf03206846
|View full text |Cite
|
Sign up to set email alerts
|

Haptic discrimination of bilateral symmetry in 2-dimensional and 3-dimensional unfamiliar displays

Abstract: In five experiments, we tested the accuracy and sensitivity of the haptic system in detecting bilateral symmetry of raised-line shapes (Experiments 1 and 2) and unfamiliar 3-D objects (Experiments 3-5) under different time constraints and different modes of exploration. Touch was moderately accurate for detecting this property in raised displays. Experiment 1 showed that asymmetric judgments were systematically more accurate than were symmetric judgements with scanning by one finger. Experiments 2 confirmed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 33 publications
5
44
1
4
Order By: Relevance
“…There could be an even more important influence on the haptic horizontal-vertical curvature illusion, aside from the haptic exploration method. It is clear that bimanual exploration aids haptic judgments of symmetry (Ballesteros et al, 1997). This benefit of bimanual exploration probably derives from allowing the individual to code patterns with respect to the body midline and use the body as a frame of reference (e.g., Millar, 2006;Millar & Al-Attar, 2002).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There could be an even more important influence on the haptic horizontal-vertical curvature illusion, aside from the haptic exploration method. It is clear that bimanual exploration aids haptic judgments of symmetry (Ballesteros et al, 1997). This benefit of bimanual exploration probably derives from allowing the individual to code patterns with respect to the body midline and use the body as a frame of reference (e.g., Millar, 2006;Millar & Al-Attar, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…It appears likely that the advantage of bimanual exploration accrued from allowing subjects the ability to make use of coding with respect to the body midline and with respect to the body itself (see Ballesteros et al, 1997;the subjects showed a slight overestimation of size (see Figure 6). …”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have investigated symmetry processing in the haptic modality using two-dimensional (2D) line drawings or three-dimensional (3D) objects as stimuli [39][40][41][42][43][44]. Overall, these studies show that although symmetry plays a role in the haptic recognition of 2D and 3D objects, symmetry is less salient for touch than it is for vision, and other stimulus properties, such as texture, may play a greater role for haptic shape discrimination compared to symmetry [43].…”
Section: Haptic Detection Of Symmetry In Normally Sighted Participantsmentioning
confidence: 99%
“…Indeed, the salience of symmetry in the haptic modality seems to be modulated by several different factors. This includes stimulus characteristics, such as material properties (e.g., texture and hardness), pattern complexity, size, dimensionality (2D/3D) and exploratory strategy [39][40][41][42][43]. Regarding exploratory strategies, symmetry detection during haptic exploration is facilitated when two hands are used [39][40][41].…”
Section: Haptic Detection Of Symmetry In Normally Sighted Participantsmentioning
confidence: 99%
See 1 more Smart Citation